Prosedur Penyelesaian Kredit Bermasalah Pada Koperasi Karya Bersama Sejahtera - Suartama, I Kadek Rully Adi; Yuniarta, Gede Adi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study will focus on how the procedure for resolving non-performing loans at the Cooperative Work Together Prosperous in 2018-2020. This research was carried out at the Cooperative Work Together Prosperous by using feasible methods including the Qualitative Descriptive Analysis method which has primary and secondary data sources through interviews and documentation. From this study, the results were obtained that the procedure for settling non-performing loans at the Cooperative Work Together Prosperous has been carried out properly and is in line with the procedures for settling non-performing loans in general. The process of settling non-performing loans at the Cooperative Work Together Prosperous is able to minimize the risk of sustainable non-performing loans. The procedure for settling non-performing loans at the Joint Works Cooperative includes: restructuring and confiscation of guarantees